Deep-State Poisoning Humanity with Toxic Waste Products - Whiteside, Mark; Herndon, J. Marvin (European Journal of Applied Sciences, 2025)
In the United States, the rate of infant mortality is highest among 46 nations, and Autism Spectrum Disorder (ASD) rates are skyrocketing. Some might consider that a great mystery, but it is not. For decades, the Deep-State has been deliberately polluting drinking-water supplies with unpurified toxic waste from phosphate fertilizer production, mainly hydrofluorosilicic acid (HFSA), under guise of improving dental health. For decades, the Deep-State has been covertly polluting the air we breathe with the toxic waste product of coal-burning, coal fly ash (CFA), wholly without public acknowledgement. Both egregious Deep-State activities must cease.